Effects of rest interval during high-repetition resistance training on strength, aerobic fitness, and repeated-sprint ability - Hill-Haas, S.; Bishop, D.; Dawson, B.; Goodman, C.; Egde, J. (Journal of Sports Sciences, 2007)
The effect of altering the rest period on adaptations to high-repetition resistance training is not well known. Eighteen active females were matched according to leg strength and repeated-sprint ability and randomly allocated to one of two groups. One group performed resistance training with 20-s rest intervals between sets, while the other group employed 80-s rest intervals between sets. Both groups performed the same total training volume and load. Each group trained 3 days a week for 5 weeks [15- to 20-repetition maximum (RM), 2 - 5 sets]. Repeated-sprint ability (5×6-s maximal cycle sprints), 3-RM leg press strength, and anthropometry were determined before and after each training programme. There was a greater improvement in repeated-sprint ability after training with 20-s rest intervals (12.5%) than after training with 80-s rest intervals (5.4%) (P = 0.030). In contrast, there were greater improvements in strength after training with 80-s rest intervals (45.9%) than after training with 20-s rest intervals (19.6%) (P = 0.010). There were no changes in anthropometry for either group following training. These results suggest that when training volume and load are matched, despite a smaller increase in strength, 5 weeks of training with short rest periods results in greater improvements in repeated-sprint ability than the same training with long rest periods.